2017
DOI: 10.5604/01.3001.0010.2340
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Different Cotton Fibre Wastes on Different Yarn Types

Abstract: In order to make a contribution to the reduction of raw material costs, in the present study the effect of reused cotton fibres on the quality of conventional ring and OE-rotor yarns was investigated. In the yarn production, it three different waste fibres were taken from a cotton yarn production line and blended with primary cotton fibres at five different levels varying from 5% to 40%. In literature, studies have concentrated on the usage of recovered waste fibre in OE-rotor yarn production. However, to date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 9 publications
0
14
0
2
Order By: Relevance
“…Telli and Babaarslan (2016) aimed to produce denim from recycled yarns without compromising on quality [10]. Yılmaz et al (2017) investigated the quality of ring and open-end yarns produced from recycled cotton fibres [11]. On the other hand, Khan et al (2015) carried out a study on the recycling of flat strips collected from carding machines in spinning mills before being pressed with a baling press machine.…”
Section: Figure 2textile Waste Categories [3]mentioning
confidence: 99%
“…Telli and Babaarslan (2016) aimed to produce denim from recycled yarns without compromising on quality [10]. Yılmaz et al (2017) investigated the quality of ring and open-end yarns produced from recycled cotton fibres [11]. On the other hand, Khan et al (2015) carried out a study on the recycling of flat strips collected from carding machines in spinning mills before being pressed with a baling press machine.…”
Section: Figure 2textile Waste Categories [3]mentioning
confidence: 99%
“…As expected, with the usage of waste fiber, the most deteriorated yarn properties were yarn unevenness in conventional ring-spun yarns and tensile properties in rotor yarns. Their findings showed that the effect of waste fiber usage on knitted fabrics' pilling behavior was significant and Pneumafil fiber blends increased the pilling resistance, while for other waste fiber blends, on the contrary [29].…”
Section: Cotton Wastes In Spinning Millmentioning
confidence: 99%
“…Yilmaz et al. [ 24 ] investigated the development of ring and OE yarn properties for waste-to-virgin fiber mixing at various ratios. However, there is a lack of investigations in the field of the rotor yarns used for sustainable economy published in the literature.…”
Section: Introductionmentioning
confidence: 99%